Performance evaluation of WirelessHART networks using a new network simulator 3 module. (January 2015) - Nobre, Marcelo; Silva, Ivanovitch; Guedes, Luiz Affonso
Abstract: Nowadays, wireless communication is a tendency in industrial environments, enabling the addition of new applications and saving resources when compared to their wired counterparts. In this context, the WirelessHART specification is emerging as a solution for the last mile connection. Despite its high degree of applicability, a WirelessHART network faces some challenges. Some of the most challenging problems are its reliability, energy consumption, and interference from the environment, issues which involve the lower layers. In order to enable performance evaluations in a low cost and scalable way, we propose a new NS-3 module for the WirelessHART physical layer including an error model (Gilbert/Elliot), station positioning, signal attenuation and energy consumption. Furthermore, the module permits configuring each link with different fault probabilities, allowing more accurate simulations. For validation, the scheduling and routing approaches were statically configured assuming different topologies and probabilistic error scenarios already validated in the literature.